Understanding Occupations of Terminally Ill Chinese Adults and Their Caregivers: A Scoping Review - Lim, Geck Hoon; Breen, Laura; Keesing, Sharon; Buchanan, Angus (Taylor & Francis, 2021)
This scoping review explored the occupations of terminally ill Chinese adults and their caregivers. Seven databases were searched for peer-reviewed journal articles published in English or Chinese before June 2020. Of the 16 studies that met the selection criteria, only one directly used the term “occupations” while the other 15 studies contained descriptions of occupations. Eight themes were extracted and compared with existing literature. The top two reported themes were occupations surrounding life roles and tasks and those surrounding food and eating. More study is required about the occupational engagement of this client group.